Almost Everyone Loses Meaning in Life From Social Exclusion, but Some More Than the Others: A Comparison Among Victims, Voluntary, and Forced Rejecters - Zhang, Shuyue; Huang, Junqing; Duan, Hedan; Turel, Ofir; He, Qinghua (Frontiers in Psychology, 2021)
Social exclusion has been a major societal concern, because it hinders the attainment of natural needs for belonging and relationship. While we know much about effects of social exclusion on victims and perpetrators, there is limited insight regarding how different motivations to perpetrate social exclusion (autonomous vs. forced) might affect important outcomes. The purpose of this study is, therefore, to bridge this gap, and to theorize and examine how different source of social exclusion ((a) forced, i.e., controlled motivation, and (b) autonomous, i.e., self-motivation) influence participants' meaning in life. To this end, we conduct two experiments using two social exclusion paradigms, namely the recall writing paradigm and the Cyberball game, as a means to increase confidence in the findings of individual experiments and paradigms. The results of the two experiments were consistent. Both studies revealed that (1) the meaning in life of the ostracized group and the controlled motivation source group (i.e., those who were forced to ostracize others) was significantly lower than that of the control group and the autonomous motivation source group (i.e., those who had autonomy over their perpetration of ostracism). There were no significant differences neither between the ostracized group and the controlled motivation source group nor between the autonomous motivation source group and the control group. These results reveal that social exclusion not only negatively affect the excluded target, but also reduces meaning in life of the controlled motivation source of exclusion.